Chloroplast Z-ring dynamics is governed by conserved core regions of evolutionarily divergent FtsZs - Cao, Lingyan; Porter, Katie J.; Du, Wenbin; Tallerday, Emily J.; Liu, Moyang; Liang, Wanqi; Osteryoung, Katherine W.; Chen, Cheng (Frontiers in Plant Science, 2025)
The chloroplast FtsZ ring (Z ring) is assembled by two distinct FtsZ proteins, FtsZ2 and FtsZ1 (referred to as FtsZA and FtsZB in red algae). FtsZ2 confers stability to the Z ring, while FtsZ1 enhances its dynamics. Enhanced Z-ring dynamics is essential for Z-ring remodeling, which drives chloroplast constriction and division. However, the mechanisms underlying the distinct dynamic properties of the two FtsZs remain unclear. Here, we report that the conserved core regions are primarily responsible for the distinct dynamic properties observed in both plant and red algal FtsZs. We demonstrate that the conserved core region of FtsZ1 enhances the dynamics of FtsZ2 within coassembled filaments. Likewise, we show that the conserved core region of red algal FtsZB promotes the dynamics of coassembled FtsZA rings. Our findings provide evidence that the evolution of a second FtsZ protein represents a general mechanism to enhance the dynamics of the chloroplast Z ring.